Rock Slope Assessment using Kinematic and Finite Element Analysis: An Example from Malekhu-Dhadingbesi Section of NH43, Central Nepal - Kafle, Nirmal; Miyan, Raju; Mishra, Aanand Kumar (Journal of Science and Engineering, 2025)
Slope stability in the Himalayas is a critical issue due to the region’s unique geological and tectonic characteristics. The rocks of Himalayas are fragile and weak due to complex deformational structures causing the instability of slopes which are common, posing significant risks to infrastructure and communities. The central Nepal is characterized by similar problems and while constructing the engineering structures, challenges might be encountered. This study is aimed at modelling slope stability along the Malekhu-Dhadingbeshi road section of NH43 lying at the central Nepal lesser Himalaya using Kinematic analysis and Finite Element Method (FEM) modelling. The FEM modelling was conducted using two different computer programs. It was carried out at six different potential slopes with multifaceted geometry composed of slightly to moderately weathered quartzites and phyllites. The potential slope sections were identified using satellite imagery and field observations with key indicators including the condition of the slope toe, the presence of dislodged rocks and the formation of tension cracks. Their geometries were then created from the survey data obtained from topographic survey in the field. Input parameters for the modeling, such as cohesion and friction angle were calculated using the Hoek-Brown criterion while unit weight, elastic modulus and uniaxial compressive strength of rocks were determined from laboratory tests. The modelling was carried out under static condition provided there are no external influences from seismic activity or water forces. Out of six identified slopes sections, three of them were found to be critical during kinematic analysis, which were further modelled using FEM. Results from FEM revealed the non-significant total displacement at all of the three slope sections with higher critical Strength Reduction Factor (SRF) making the slopes stable. The findings also highlight the strength of the slopes under current conditions, providing valuable information for infrastructure planning in the region.